Space Econometry: new techniques for the regional analysis. An application to the European regions - Esther Vayá Valcarcel (Investigaciones Regionales - Journal of Regional Research, 2002)
The goal of this paper is helping in the diffusion in our country of the techniques given by Spatial Econometrics, offering an overview of its theoretical and applied aspects. Specifically, we introduce the two types of spatial data analysis: the exploratory analysis, focused on a univariate study, as well as the study of spatial autocorrelation in a regression model. Additionally, we apply some of the techniques to the case of the European Union regions.